GPS analysis of elite women's field hockey training and competition - Gabbett, T. J. (The Journal of Strength and Conditioning Research, 2010)
This study investigated the physiological demands of women's field hockey competition and compared these demands to those experienced during game-based training activities. Fourteen elite women field hockey players (mean ± SD; age, 23.3 ± 3.2 years; maximal oxygen consumption, 53.5 ± 4.3 ml/kg·min) participated in this study. Global positioning satellite (GPS) system analysis was completed during 19 training appearances and 32 Australian Hockey League (AHL) appearances. All training sessions consisted of game-based activities (i.e., small-sided training games) that were played on a reduced-sized pitch. Movement was recorded by a global positioning satellite unit sampling at 5 Hz. Data were categorized into discreet movement velocity bands, corresponding to low-intensity (0-1 m/s), moderate-intensity (1-3 m/s and 3-5 m/s), and high-intensity (5-7 m/s and >7 m/s) activities. Players covered 6.6 km (range: 3.4-9.5 km) over the course of the match. Midfielders spent more time and covered greater distances in high-intensity running (i.e., >5 m/s) than strikers and defenders. The number of high-velocity and high-acceleration efforts over the course of a match was greater in midfielders. In comparison to competition, game-based training sessions resulted in more time spent in low-intensity (i.e., 0-1 m/s) activities and less time spent in moderate (i.e., 1-3 m/s and 3-5 m/s) and high-intensity (i.e., 5-7 m/s and >7 m/s) activities. Although game-based training is likely to be useful for improving the skill levels of players, the skill activities used in the present study did not reflect the physiological demands of competition, with players spending more time in low-intensity activities and less time in high-intensity activities than competition. Modifications in training group size and/or drill design and complexity may better simulate the physiological demands of competition.